A influência dos movimentos sociais na reconfiguração das identidades : um estudo junto aos reassentados pela construção da Usina Hidrelétrica de Salto Caxias - PR - Derrosso, Giuliano Silveira (2012)
This dissertation addresses the influence of the social movements that were operating at the time that the hydroelectric power plant of Salto Caxias (Paraná) was built and their impact on the reconfiguration of Identity of the Riparians who were compulsorily displaced. Salto Caxias is one of the power plants owned by COPEL, and it was built on the Iguassu River after approximately 140 m2 of area was flooded in order to build its reservoir. As a consequence, more than a thousand families were displaced. In this context, we attempted to comprehend the topic of identity focusing on different authors' perspectives, as well as discussing personal and social identities and how the process of construction of a new identity occurs. Also addressed was the constitution and organization of these social movements and their actions, analyzing their specific role on the construction of the hydroelectric power plant of Salto Caxias/PR. Having as a goal to understand how these social movements influenced the change on the displaced persons' identities, we conducted interviews of thematic oral history, trying to recapture through speech, the memories of that time and the effects on the subjects. In the case of Salto Caxias, we found that the sense of collective struggle fostered by the foundation of CRABI pervaded the processes of change of identity, and the effective participation of the displaced population in the institution made possible the achievement of better conditions to face the situation. Thus it was possible to understand how the CRABI marked the lives of those individuals and worked in favor of a common good through shared ideologies and values.